A novel integration of pd-type fuzzy logic controllers and smes devices to maintain the network frequency of a large-scale power system - Thuan, Vu Duy; Khoat, Nguyen Ngoc; Nhan, Hoang Ngoc; Vinh, Thai Quang; Tan, Ngo Sy (Journal of Computer Science and Cybernetics, 2017)
A modern electric power plant is typically considered to be a large-scale system. Due to continual and random occurrence of load changes, maintenance of network frequency (or load frequency control – LFC) at its nominal value is one of the most crucial control problems in order to ensure the stability and reliability of such an electric power grid. This study investigates a newly efficient integration of fuzzy logic controllers based on PD principle and superconducting magnetic energy storage (SMES) devices in an effort to protect the system frequency from the load variations. It is well known that the PD-based fuzzy logic controllers, when applied to an LFC strategy, are capable of damping quickly the oscillations of both the system frequency and tie-line power deviations. In addition, the load disturbances can be compensated if the network is applying the SMES devices. Therefore, the integration between them might become an efficiently feasible solution for the LFC issue. The superiority of the proposed control methodology over conventional regulators is verified through a number of numerical simulations which will be implemented in this study for a five-area electric power grid model.